REIMAGINING THE FUTURE OF ACTIVE AGEING AMONGST ELDERLY : (Leading an Inclusive and Quality Life in Muslim Retirement Village) - Abdul Mutalib, Mashitah (PROCEEDING AL GHAZALI International Conference, 2023)
This study looks at the quality of life experienced by residents of Muslim retirement village, Madrasah Ibnu Mas'ud Nilai (MIMNI). This institution started in 2019 with the aim of helping the elderly to enjoy a quality life, especially after their retirement. The main question of this study is to examine whether the atmosphere and activities in this institution help the elderly enjoy a quality life. The study is a qualitative study employing document analysis. Interview with the management of MIMNI was also conducted to obtain first hand information on this Muslim retirement village. This paper finds that Muslim retirement village provides an avenue for the elderly to enjoy quality and active ageing. Nevertheless, support and aids from the authorities are needed to ensure that these institutions can sustain and provide more benefits to higher numbers of senior citizens. This paper shall assist the policy makers in enhancing the policy on older people particularly on the establishment of retirement village.